Floristic composition and structure of Cerrado restricted sense in the Chapada Diamantina, Palmeiras, Bahia, Brazil - Costa, Grênivel Mota da; Funch, Lígia Silveira; Conceição, Abel Augusto (SITIENTIBUS série Ciências Biológicas, 2009)
This paper aims to characterize the floristic composition and structure of the woody component of an area of ‘cerrado’ sensu stricto in the Chapada Diamantina, in the municipality of Palmeiras, Bahia (12º27’30.9"S and 41º27’28.3"W), 800 m of altitude. The floristic survey included all species in the area, while characterization of the structure was restricted to the woody component sampled in five randomly demarcated plots 20x50m (5000m2), measuring all the individuals with the perimeter to ground height less than 5 cm. We found 89 species, distributed in 69 genera and 38 families. The families richest in species are Fabaceae, Asteraceae, Rubiaceae and Myrtaceae. The woody component characterized for the structure included 37 species, being the average density of 418 individuals per hectare and basal area average of 1.69 m2/ha. The families with the highest values of importance were Myrsinaceae, Euphorbiaceae and Fabaceae, relating mainly to the high densities of species.